Hot deformation and dynamic recrystallization behavior of a powder metallurgy Ti‐45Al‐6Nb‐0.3W alloy. Issue 5 (14th May 2021) - Yang, Dongye; Liu, Na; Gu, Xu; Ma, Pan; Zhang, Guoqing; Sun, Jianfei
Abstract: The flow behaviors of powder metallurgy (PM) Ti‐45Al‐6Nb‐0.3W (at.%) alloy were systematically investigated in the temperature range from1050 to 1200°Cand the strain rates from 0.001 to 0.5 s −1 . The effects of the temperature and the strain rate on deformation behaviors were represented by Zener–Hollomon parameter in an exponent‐type equation. Microstructural observations revealed that α2 /γ lamellar colonies varied into particle α2 due to dynamic recrystallization (DRX) at high temperature during the compression. The result indicated that the strain‐dependent constitutive equation could lead to a good agreement between the calculated and measured flow stresses in the elevated temperature range for the PM Ti‐45Al‐6Nb‐0.3W alloy. Subsequently, the correlation coefficient ( R ) and the average absolute relative error ( AARE ) were introduced to verify the validity of the constitutive equation, and values of R and AARE were 0.99483 and 3.956%, respectively.